THE IMPLEMENTATION OF DECISION-MAKING PROCESSES IN THE GOVERNMENT OF GUWOSARI VILLAGE, YOGYAKARTA PROVINCE. - Agus Priyanto (Post Graduate School of Government Science, 2025)
The decision-making process in village governance plays a crucial role in realizing good governance and enhancing community participation in village development. The Government of Guwosari Village represents one example of a village that seeks to implement these principles in its daily governance practices. This study aims to analyze the implementation of the decision-making process in the Government of Guwosari Village. This research employs a descriptive qualitative approach. The research informants consist of village officials, community leaders, and members of the general public. Data were collected through interviews and document analysis, particularly the official website of the Guwosari Village Government, and were analyzed using descriptive qualitative analysis. The results indicate that: (1) the decision-making process in Guwosari Village reflects an open, visionary, and participatory leadership pattern; (2) deliberative mechanisms are conducted in stages, from the hamlet level to the village level, actively involving the community; and (3) the village government applies the principles of transparency and accountability by providing channels for complaints and the expression of public aspirations, both directly and online. These findings demonstrate that the Government of Guwosari Village has implemented the principles of good governance, and that a responsive and open decision-making system can serve as a model for other village governments in formulating policies that are widely accepted by the community.